From neuroleadership to the achieving organizational goals. A reflective approach as a management process. (Ágora de Heterodoxias, 2026)
Neuroliderazgo constitutes a fundamental managerial tool that emphasizes knowledge of brain functioning in order to understand human behavior and support organizations in the development of more effective strategies (Nakamura, Silva & Santos, 2023). This approach aims to equip organizations with competencies that enable them to respond to contemporary challenges. Therefore, the objective of this essay is to examine how neuroliderazgo can be implemented effectively. In this sense, it seeks to evaluate a series of steps that can be progressively managed within organizations to optimize results and enhance organizational performance.
Keywords: Neuroleadership,; Process; Institutional Objectives; Economic Growth